ASSESSMENT OF BENGAWAN SOLO RIVER RAW WATER QUALITY USING THE POLLUTION INDEX - Intan Ayu Pebiola; Heri Mulyanti; Laily Agustina Rahmawati (Jurusan Kimia FMIPA Universitas Lampung, 2025)
The Bengawan Solo River is a primary water resource in Central and East Java. Human activities along the Watershed (DAS) have affected water quality. This study evaluates the water quality of the Bengawan Solo River during the dry and rainy seasons from 2019 to 2023 using the Pollution Index (IP) method, based on secondary data from Perum Jasa Tirta I at four locations: upstream, middle, downstream 1, and downstream 2. The analyzed parameters include physical (temperature, TDS, TSS), chemical (pH, DO, BOD, nitrate), and biological (Total coliform) aspects. The results indicate that pH, TDS, and nitrate remain within quality standards, whereas temperature, BOD, DO, and TSS often exceed the limits, especially during the rainy season. The Pollution Index (Pij) suggests better water quality in the dry season, predominantly classified as